Clinical and pathological characteristics of early-onset colorectal cancer in South Korea - Su Bee Park; Jin Young Yoon; Min Seob Kwak; Jae Myung Cha (The Saudi Journal of Gastroenterology, 2023)
Background: Early-onset colorectal cancer (EOCRC) may differ by race and ethnicity, and recently South Korea has witnessed a surge in cases. We aimed to evaluate the clinical and pathological features of patients with EOCRC, and to determine the predictors of overall survival. Methods: In this retrospective study, EOCRC was defined as CRC diagnosed in patients aged < 50 years, and late-onset CRC was defined as CRC diagnosed in those over 75 years of age. The clinical and pathological characteristics of patients with EOCRC were compared with late-onset CRC. We also used multivariable Cox proportional hazard models to find predictors of overall survival in patients with EOCRC. Results: The proportion of early-onset CRC was 9.1% of 518 patients with CRC, and the clinical and pathological characteristics were similar between early-onset (n = 47) and late-onset CRC (n = 134). However, EOCRC had a preponderance for distal tumor location (70.2% vs. 50.7%, P = 0.02) and T1-2 stage disease (23.4% vs. 11.2%, P = 0.04), compared with those of late-onset CRC. Using multivariable Cox proportional hazard models, only vascular invasion (hazard ratio = 8.75, 95% confidence interval 1.139‒67.197) was found to be a risk factor for overall survival (P = 0.04) for patients with CRC. Conclusion: EOCRC had preponderance for distal tumor location and early T-stage disease, compared with late-onset CRC. Considering the increasing incidence of EOCRC, more studies on clinical and pathological characteristics of EOCRC may be warranted.